2005
DOI: 10.1038/sj.emboj.7600528
|View full text |Cite
|
Sign up to set email alerts
|

E47 phosphorylation by p38 MAPK promotes MyoD/E47 association and muscle-specific gene transcription

Abstract: Selective recognition of the E-box sequences on muscle gene promoters by heterodimers of myogenic basic helixloop-helix (bHLH) transcription factors, such as MyoD, with the ubiquitous bHLH proteins E12 and E47 is a key event in skeletal myogenesis. However, homodimers of MyoD or E47 are unable of binding to and activating muscle chromatin targets, suggesting that formation of functional MyoD/E47 heterodimers is pivotal in controlling muscle transcription. Here we show that p38 MAPK, whose activity is essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
142
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(147 citation statements)
references
References 33 publications
1
142
2
Order By: Relevance
“…MAP kinase-induced MyoD and E47 heterodimerization and muscle-specific gene transcription (Lluis et al, 2005). However, the evaluation of E47S133AHA stability revealed no correlation between Ser133 phosphorylation and E47 degradation.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…MAP kinase-induced MyoD and E47 heterodimerization and muscle-specific gene transcription (Lluis et al, 2005). However, the evaluation of E47S133AHA stability revealed no correlation between Ser133 phosphorylation and E47 degradation.…”
Section: Resultsmentioning
confidence: 88%
“…This suggests that the E2A proteins may be relatively spared whereas forming active transcriptional complexes with muscle regulatory factors during the initiation and maintenance of muscle differentiation. Previous electrophoresis mobility shift analyses have shown that E2A/MyoD/Ebox-DNA complexes only form after the initiation of muscle differentiation (Lluis et al, 2005). In proliferating myoblasts, rapid turnover of the E2A proteins may prevent the cells from the commitment for differentiation.…”
Section: E2a Protein Degradation In Muscle Differentiation L Sun Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has demonstrated that p38 MAPK activates muscle-specific gene transcription. Phosphorylation of E47 at Ser 140 by p38 MAPK enhances MyoD/E47 heterodimerization and subsequent binding to E-box sequences (12). Other results may suggest that p38 MAPK could exert a negative effect by phosphorylating other residues in the N terminus of E47 (13).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that phosphorylation status of E47 alters the DNA binding ability of E47 as homodimers or heterodimers in different cellular contexts (9 -11). Thus, p38 MAPK has been described to phosphorylate E47 at Ser 140 and promote MyoD/E47 association and muscle-specific gene transcription (12). On the other hand, it has also been observed that MEKK1 (MAPK/ERK kinase kinase 1) signaling through p38 leads to transcriptional inactivation of E47 (13).…”
mentioning
confidence: 99%